Pengaruh Edukasi Gizi Mengenai Anemia Dengan Media Video Terhadap Pengetahuan Dan Sikap Remaja Putri Di SMAN 1 Nganjuk - Nadela Novita Sari; Sugeng Iwan Setyobudi; Tapriadi Tapriadi (Politeknik Kesehatan Kemenkes Malang, 2022)
Adolescents are one of the age groups that are prone to problems. One of the most common nutritional problems is anemia. Riskesdas 2018 prevalence of anemia in Indonesia is 23.7 percent, based on the age group 15 sampai 24 it is 32 percent. While the prevalence of anemia in women is 27.2 percent and in men is 20.3 percent. This nutrition education aims to change the knowledge and attitudes of young women and provide information about anemia to prevent anemia. The selection of video media adapts to the character of teenagers who are interested in interesting things and are very easily bored. Objectives: to study and determine the effect of nutrition education on anemia with video media on the knowledge and attitudes of young women about anemia at SMAN 1 Nganjuk. Methods: This is a quasi experimental study with a non equivalent control group design. The research sample was 30 respondents in the control and treatment groups with a purposive sampling technique. Data processing using SPSS application. Statistical analysis using the Kolmogorov Smirnov, Wilcoxon, paired sample t test, and Umann Whitney test. Result: The results showed that there were differences in knowledge and attitudes before and after education in the treatment group (p less than 0.05). There was no difference before and after education in the control group (p more than 0.05). There are differences in knowledge and attitudes between the treatment and control groups Conclusion: There are differences in knowledge and attitudes between the treatment and control groups KEYWORDS: NUTRITION EDUCATION, ANEMIA, VIDEO, KNOWLEDGE, ATTITUDE, ADOLESCENT GIRLS